2012
DOI: 10.1063/1.4729658
|View full text |Cite
|
Sign up to set email alerts
|

Aspect ratio effects on neoclassical tearing modes from comparison between DIII-D and National Spherical Torus Experiment

Abstract: Neoclassical tearing mode islands are sustained by helically perturbed bootstrap currents arising at finite beta from toroidal effects that trap a fraction of the particles in non-circulating orbits. DIII-D and NSTX are here operated with similar shape and cross-sectional area but almost a factor of two difference in inverse aspect ratio a=R. In these experiments, destabilized n ¼ 1 tearing modes were self-stabilized (reached the "marginal point") by reducing neutral-beam power and thus beta. The measure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 43 publications
5
27
0
Order By: Relevance
“…This kind of behaviour at w ∼ ρ ϑi is the direct result of the inclusion of the drift islands in our model and is in agreement (qualitative and quantitative) with experimentally observed self-healing of small magnetic islands below the threshold (e.g. [33]). A straight line fit shown in the inset of figure 8.…”
Section: Neoclassical Drive For Ntmssupporting
confidence: 88%
See 1 more Smart Citation
“…This kind of behaviour at w ∼ ρ ϑi is the direct result of the inclusion of the drift islands in our model and is in agreement (qualitative and quantitative) with experimentally observed self-healing of small magnetic islands below the threshold (e.g. [33]). A straight line fit shown in the inset of figure 8.…”
Section: Neoclassical Drive For Ntmssupporting
confidence: 88%
“…However, in [32] it has been shown that the marginal island width below which the NTM is removed, i.e. dw/dt < 0, is about 2ρ bi in both ECCD and beta rampdown discharges and is about 3ρ bi in [33]. This is exactly the region where the existing theory breaks down.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, a comparison experiment between NSTX and DIII-D indeed showed the magnetic curvature stabilizing term to be important for NSTX parameters. 112 Overall, NTMs in ST plasmas therefore appear to be more stable than in conventional tokamaks. Another important feature is the projected high f BS ST reactor q profile [shown, for example, in Fig.…”
Section: Neo-classical Tearing Modesmentioning
confidence: 99%
“…[73,74] studied a class of m/n=2/1 magnetic islands, and showed that they had many characteristics of 2/1 neoclassical tearing mode. Ref.…”
Section: : Onset Of Core N=1 Activitymentioning
confidence: 99%